The response of layered anisotropic tubes to centrifugal loading. - Carpenter, H.W.; Reid, R.G. (Elsevier, 2016)
The displacement-based elastic solution for layered anisotropic tubes is extended to allow for the presence of centrifugal loading. The additional terms in the stress-strain equations derived in this work are validated by comparing the results obtained using the current solution against those determined using finite element simulation of rotating thin and thick-walled glass fibre reinforced plastic tubes of arbitrary anisotropic lay-up. The solution is presented in such a form that it can be utilised to determine the linear thermo-mechanical behaviour of rotating tubes with anisotropic lay-up, subjected to any combination of internal and external axisymmetric pressure, axial loading, torsional loading, and constant temperature change.
Pre-print
Keywords: Anisotropic tubes; Centrifugal Loading; Elastic Solution; Fiber reinforced plastics; Finite element method; Stress-strain equations; Thermo-mechanical; Torsional loadings